Application of Burden of Proof to Child Labour as Protection of Children's Rights - Ahmad Fauzi; M. Noor Fajar Al Arif F (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2023)
Child labour should be given legal protection, one form of protection for child labour is to impose a Burden of Proof (Burden of Proof) for child labour in accordance with the provisions of the ILO Convention (International Labor Organization) No. 138 of 1973 on the minimum age to be allowed to work and the ILO (International Labour Organization) Convention No. 183 then 1999 on the abolition of the worst forms of work for. This research aims to examine the philosophical foundation of the burden of proof in the Indonesian legal system and to examine the burden of proof implementation for child labour in Indonesia. This research is legal research using a normative juridical approach, the data used are primary data and secondary data analyzed using quantitative analysis. The results of the study are the first philosophical application of the principle of reverse burden of proof that has been regulated in various legal rules in Indonesia, including Law No. 8 of 1999 on Consumer Protection, Law No. 40 of 2007 concerning limited Company legal No. 32 of 2009 on the protection and management of the environment and the provisions of the crime of corruption relating to the freezing, expropriation and confiscation of the perpetrators of the crime of corruption in accordance. Both countries have ratified ILO Convention No. 138 of 1973 on the Minimum age to be allowed to work and ILO Convention No. 182 of 1999 on the Prohibition and immediate action on the elimination of the worst forms of Child Labour which affirms the existence of a reverse proof for child labour.